How beautiful we were : a novel - Mbue, Imbolo (Random House, 2021)
"'We should have known the end was near." So begins Imbolo Mbue's exquisite and devastating novel 'How Beautiful We Were.' Set in the fictional African village of Kosawa, it tells the story of a people living in fear amidst environmental degradation wrought by a large and powerful American oil company. Pipeline spills have rendered farmlands infertile. Children are dying from drinking toxic water. Promises of clean up and financial reparations to the villagers are made--and ignored. The country's government, led by a corrupt, brazen dictator, exists to serve its own interest. Left with few choices, the people of Kosawa decide to fight the American corporation. Doing so will come at a steep price. Told through multiple perspectives and centered around a fierce young girl named Thula who grows up to become a revolutionary, Joy of the Oppressed is a masterful exploration of what happens when the reckless drive for profit, coupled with the ghosts of colonialism, comes up against one village's quest for justice--and a young woman's willingness to sacrifice everything for the sake of her people's freedom"--